ON UPPER AND LOWER WEAKLY \(\mathcal{I}\)-CONTINUOUS MULTIFUNCTIONS - Arivazhagi, C.; Rajesh, N. (Italian Journal of Pure and Applied Mathematics, 2016)
In this paper, we introduce and study a new generalization of \(\mathcal{I}\)-continuous multifunctions called weakly \(\mathcal{I}\)-continuous multifunctions in topological spaces.